Molecular Exchange of Dynamic Imine Bond for the Etching of Polymer Particles. Issue 23 (11th August 2022) - Mao, Jie; Wu, Tong; Tang, Zhenbin; Xia, Long; He, Liu; Zeng, Birong; Xu, Yiting; Yuan, Conghui; Dai, Lizong
Abstract: The underlying trend of colloidal synthesis has focused on extending the structure and composition complexity of colloidal particles. Hollow and yolk–shell particles are successful examples that have potential applications in frontier fields. In this paper, a facile and controllable etching method based on the molecular exchange of the dynamic imine bond to generate cavities in polymer particles is developed. Starting from boronate ester polymer particles and inorganic@boronate core–shell particles with the imine bonds incorporated in the polymer networks, the etching method easily affords hollow and yolk–shell particles with tunable shell thicknesses. The molecular exchange dynamics analysis indicates that guest amine molecules cause the reconstruction of imine bonds and the leakage of molecular and oligomer fragments, resulting in the formation of the hollow structure. This molecular exchange‐based etching method may be of interest in the construction of polymer architectures with increased composition and structure complexities. Abstract : Herein, a facile and general etching method based on the molecular exchange of the dynamic imine bond to create cavities in polymer particles is developed. This method offers a high capability for etching dynamics control, leading to the formation of hollow and yolk–shell particles with tunable shell thicknesses and cavity sizes.